Spanish borrowing into Emberá (2022)
eng: Emberá is a Central American Indian language belonging to the Choco grouping. This study is based on information from elicitations obtained from Mr. Daniel Castañeda, a Panamanian native speaker of Emberá. The number of speakers of Emberá is unequally distributed across Panama, Colombia, and Ecuador. Though the statistics vary, the number of native speakers is no more than sixty thousand, in toto, and in Panama, the number of speakers is about twenty thousand. This study is the first attempt to collect and analyze the basic lexical items of the language, and it is the first in English and Spanish. All elicitations were done through the medium of Spanish, at Georgetown University in Washington, D. C., while Mr. Castañeda was residing in the area. For convenient reference, all examples will be given in Spanish, Emberá. and English. The phonological changes observed here are quite varied. This is not an exhaustive study, but it does illustrate both the frequent and the sporadic changes in the Spanish words as they are incorporated into Emberá.